1999
DOI: 10.1016/s0038-0717(99)00116-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon mineralization dynamics in soils after wildfires in two Galician forests

Abstract: The carbon mineralization dynamics of two Humic Cambisols, developed over granite, one under Pinus sylvestris L. (1740 m a.s.l.) and the other under Pinus pinaster Aiton (140 m a.s.l.), were determined in samples of 0±5 and 5±10 cm depth collected after high intensity wild®res. Burnt and unburnt soils were sampled ®ve times over 2 yr after the wild®res to determine changes in C concentration and in potential mineralization activity of the soil organic matter. Soil samples from the same forests unaected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 27 publications
7
37
0
Order By: Relevance
“…Wildfires modify quantitatively and qualitatively the soil C and N pools (Castro et al 2006;Certini et al 2011;Fernández et al 1997Fernández et al , 1999 that are the energy source for heterotrophs and the substrate for N transformations, respectively. Although weak relations have also been reported (Gómez-Rey et al 2012), the soil C and N pools are considered to be important controlling factors of gross N transformations (Booth et al 2005;Lang et al 2010;Magill and Aber 2000), with which they showed moderate to strong correlations in our plots.…”
Section: Discussionmentioning
confidence: 99%
“…Wildfires modify quantitatively and qualitatively the soil C and N pools (Castro et al 2006;Certini et al 2011;Fernández et al 1997Fernández et al , 1999 that are the energy source for heterotrophs and the substrate for N transformations, respectively. Although weak relations have also been reported (Gómez-Rey et al 2012), the soil C and N pools are considered to be important controlling factors of gross N transformations (Booth et al 2005;Lang et al 2010;Magill and Aber 2000), with which they showed moderate to strong correlations in our plots.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of controlled burning on soil C release is more complex than that of brush clearing. Compared to brush clearing, controlled burning can affect soil C release not only during the burning process but also during the post-burning period (Fernández et al, 1999). During the burning process, 60-80% of the surface organic materials are burned out and revert to the atmosphere as CO 2 (González-Pérez et al, 2004), leading to a remarkable decrease in soil C stock (Guo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Semi-arid woodlands are frequently exposed to fire, which changes not only vegetation structure and communities but also soil properties such as reducing soil organic matter content and increasing recalcitrance of the remaining organic matter (Fernandez et al, 1999;Hatten and Zabowski, 2009). These changes in soil organic matter content and recalcitrance could also influence the response of respiration to drying and rewetting.…”
Section: Introductionmentioning
confidence: 99%